A note on potential candidate genomic regions with implications for maize stover fodder quality - Vinayan, M.T.; Babu, R.; Jyothsna, T.; Zaidi, Pervez Haider; Blümmel, Michael (Elsevier, 2013)
Panel of inbred lines were test crossed to a tester CML312SR and evaluated for stover fodder quality and agronomic traits. These lines were genotyped for by SNP's (55 K illumine and GBS) and 445 K SNP marker were used for GWAS for Stover N, ADF and IVOMD. Significant desirable and undesirable trait relationships between stover quality traits were identified. An ensemble of putative genomic regions in maize contributing to these traits identified for further evaluations.